The scientific capabilities of the Evanescent Wave Coronagraph EvWaCo. Issue 1 (1st January 2023) - Ridsdill-Smith, M; Berdeu, A; Alagao, M A; Buisset, C; Awiphan, S
Abstract: The Evanescent Wave Coronagraph, EvWaCo, is an in-development prototype coronagraph, designed for use on the 2.4m Thai National Telescope (TNT), in the R and I-band filters. This work examines the astronomical capabilities of EvWaCo using the results from Fourier-analysis simulations. Fourier optics simulations were applied to the EvWaCo prototype to analyse its performance, combining different sources of contrast degradation that will be present in the system. The simulations used for the main analysis assume a good night at the Thai National Observatory (TNO) and include the fitting error, aliasing, measurement noise and lag, providing a radially averaged contrast curve. From the contrast curve, the detection limit, as defined by a minimum signal to noise ratio of 5 for a typical observation time, can be calculated for different primary star magnitudes. The relative fluxes of various binary stars, with a range of spectral classes and separations, were modelled allowing comparison to the EvWaCo detection curves. The photon-noise limited detection curves provide a theoretical baseline for the performance that will be achieved with EvWaCo; they, therefore, give an indication of the types of objects EvWaCo can observe. Along with a broader discussion of observable objects, a number of known binary systems are suggested for observations on the TNT using EvWaCo.